Physical and Physiological Quality of Rice Seeds of Inpari 32 Variety Under Different Harvest Ages, Packaging Types, and Storage Durations - Arif Fathoni; Ramdan Hidayat; Juli Santoso (The University of Lampung, 2025)
This study aimed to determine the optimal harvest time and packaging type to preserve the quality of Inpari 32 rice seeds during storage. Conducted at the Food and Horticultural Plant Seed Supervision and Certification Unit in East Java from November 2023 to April 2024, the research used a factorial experiment in a completely randomized design (CRD) with three replications. Harvest age treatments were 110, 120, 130, and 140 days after seedling (DAS), while packaging types included plastic sacks, polyethylene (PE) sacks, polypropylene (PP) sacks, and aluminium foil. Data were analyzed using ANOVA and Duncan's Multiple Range Test (DMRT) at a 5% significance level. Results showed that harvesting at 120 DAS with PP sacks yielded the highest starch content, while 140 DAS with aluminium foil resulted in the lowest reducing sugar content. Optimal germination and growth speed were achieved at 130 DAS, which also minimized electrical conductivity. Harvesting at 140 DAS produced the highest 1000-grain weight. Aluminium foil packaging maintained the lowest moisture content and significantly improved germination and growth speed compared to other packaging types. These findings suggest that optimizing harvest age and packaging type can significantly improve seed viability and storage performance.